Feasibility and Added Value of Fetal DTI Tractography in the Evaluation of an Isolated Short Corpus Callosum: Preliminary Results - Millischer, A.-E.; Grevent, D.; Sonigo, P.; Bahi-Buisson, N.; Desguerre, I.; Mahallati, H.; Bault, J.-P.; Quibel, T.; Couderc, S.; Moutard, M.-L.; Julien, E.; Dangouloff, V.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Prognosis of isolated short corpus callosum is challenging. Our aim was to assess whether fetal DTI tractography can distinguish callosal dysplasia from variants of normal callosal development in fetuses with an isolated short corpus callosum.MATERIALS AND METHODS: This was a retrospective study of 37 cases referred for fetal DTI at 30.4 weeks (range, 25–34 weeks) because of an isolated short corpus callosum  less than the 5th percentile by sonography at 26 weeks (range, 22–31 weeks). Tractography quality, the presence of Probst bundles, dysmorphic frontal horns, callosal length (internal cranial occipitofrontal dimension/length of the corpus callosum ratio), and callosal thickness were assessed. Cytogenetic data and neurodevelopmental follow-up were systematically reviewed.RESULTS: Thirty-three of 37 fetal DTIs distinguished the 2 groups: those with Probst bundles (Probst bundles+) in 13/33 cases (40%) and without Probst bundles (Probst bundles–) in 20/33 cases (60%). Internal cranial occipitofrontal dimension/length of the corpus callosum was significantly higher in Probst bundles+ than in Probst bundles–, with a threshold value determined at 3.75 for a sensitivity of 92% (95% CI, 77%–100%) and specificity of 85% (95% CI, 63%–100%). Callosal lipomas (4/4) were all in the Probst bundles– group. More genetic anomalies were found in the Probst bundles+ than in Probst bundles– group (23% versus 10%, P = .08).CONCLUSIONS: Fetal DTI, combined with anatomic, cytogenetic, and clinical characteristics could suggest the possibility of classifying an isolated short corpus callosum as callosal dysplasia and a variant of normal callosal development.CCcorpus callosumFAfractional anisotropyfDTIfetal DTIfMRIfetal MR imagingICOFD/LCCinternal cranial occipitofrontal dimension/length of the corpus callosumISCCisolated short corpus callosumIQRinterquartile rangePBProbst bundlesSCCshort corpus callosum